2019
DOI: 10.3390/ma12101725
|View full text |Cite
|
Sign up to set email alerts
|

Nanomelanin Potentially Protects the Spleen from Radiotherapy-Associated Damage and Enhances Immunoactivity in Tumor-Bearing Mice

Abstract: Radiotherapy side-effects present serious problems in cancer treatment. Melanin, a natural polymer with low toxicity, is considered as a potential radio-protector; however, its application as an agent against irradiation during cancer treatment has still received little attention. In this study, nanomelanin particles were prepared, characterized and applied in protecting the spleens of tumor-bearing mice irradiated with X-rays. These nanoparticles had sizes varying in the range of 80–200 nm and contained sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, melanization is considered a survival strategy for many organisms inhabiting unfavorable environmental conditions. Owing to the multifunctionality of the pigment, it has been known to serve as: (a) an antioxidant and radical scavenger (Ju et al 2011 ; Le Na et al 2019 ), (b) a photo-protector that efficiently absorbs and dissipates solar radiation in the form of heat (d’Ischia et al 2015 ), (c) an absorber that chelates metals and binds organic compounds (Karlsson and Lindquist 2016 ; Tran-Ly et al 2020 ) and (d) an organic semiconductor (Bothma et al 2008 ). Besides these functions, melanin is considered eco-friendly and biocompatible since it is naturally synthesized by most organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, melanization is considered a survival strategy for many organisms inhabiting unfavorable environmental conditions. Owing to the multifunctionality of the pigment, it has been known to serve as: (a) an antioxidant and radical scavenger (Ju et al 2011 ; Le Na et al 2019 ), (b) a photo-protector that efficiently absorbs and dissipates solar radiation in the form of heat (d’Ischia et al 2015 ), (c) an absorber that chelates metals and binds organic compounds (Karlsson and Lindquist 2016 ; Tran-Ly et al 2020 ) and (d) an organic semiconductor (Bothma et al 2008 ). Besides these functions, melanin is considered eco-friendly and biocompatible since it is naturally synthesized by most organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that splenic irradiation can cause radiation-related lymphopenia and damage the immune function, which adversely affects the body. [ 23 , 24 ] However, some studies have indicated that radiation-related lymphopenia does not affect the overall survival rate of patients. [ 17 ] Some studies suggest that tumor irradiation combined with spleen irradiation can result in additional T cell aggregation in the tumor microenvironment, which assists with controlling tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MEL-NPs can be produced both by biological extraction, which resorts to the direct separation and purification of spherical NPs from natural sources, and chemical synthesis. For instance, Le Na et al obtained nanomelanin particles by dissolving commercial melanin powder in alkaline solvents (i.e., sodium and/or ammonium hydroxide) and neutralizing the solution using hydrochloride acid [ 92 ]. Artificially synthesized polydopamine nanoparticles (PDA-NPs) mimic natural melanin, possessing similar properties but provide better controllability.…”
Section: Melanin-based Targeted Cancer Therapymentioning
confidence: 99%